The Development of Translation Theory - Cesar A. Hidalgo (Journal of Modern Languages)
This study presents a periodization of the development of translation theory. Five major periods are presented from ancient times to the present. The estimated dates given represent heights in the consideration of issues in translation or period of dominance of certain issues. Even as some of these issues cut across periods, the heights should circumscribe the limitations and breadth of the various theoretical periods.